FishBase: SealifeBase Symposium 2022 (Day 2) - Tilley, Alexander (WorldFish, 2023)
This symposium was an opportunity to illustrate the different uses of FishBase and SeaLifeBase in ecology, biogeography, fisheries, taxonomy and aquariology. It will highlight the contribution of these two global information systems to the knowledge of biodiversity and the sustainable use of aquatic ecosystems, and those from various other databases.